Privatsfærens informatisering: Nogle bidrag til udmåling af afstande mellem 1484 og1984 - Bjerg, Kresten (Psyke & Logos, 2023)
The author reports from a summer 1984 sojourn in an old farm in the Asconian woodsin Sweden with af computer-audio-visual protoype ("Domestic Information Manipulation Systems") from the D. I. M. S/Experimental Home - project at the Psychological Laboratory, University of Copenhagen. He considers the necessities of a demand for essential datanetwork-intependency in a Scandinavian concept and design of the "common private household multimedium" of tomorrow. Further areas of demand are illustrated from considerations of previously accumulated tools, bits and pieces in the information-ecology of the farm and general problems of crossgenerational rearrangement and reconstruction there. A brief account of project-outlines and rationale behind the mentioned R&D-project is given, and the imminent problems of the processes considered are interpreted as phenomena and targets of decision in cultural history, to be seen in a 500-years perspective. This is illustrated with reference to the triptych "Las Fresas" or "The Garden of Delights" by Hieronymus Bosch, which exemplifies important dimensionalities, which a domestic knowledge-data-base editing system must be able to incorporate and make users able to handle.